Perencanaan Arsitektur Enterprise Pada Universitas Islam Riau Menggunakan Zachman Framework - Mulyana, Wide; Setiawan, Rangga (Department of Information System Muhammadiyah University of Riau, 2023)
Higher education is one of the organizations that has a pretty complicated business process, in which each department has the obligation to coordinate closely with one another, exchange data, make reports, conduct calculations, and make executive summaries as material for leaders to use in the formation of policies. On the other hand, certain industries have developed information systems that are constructed in a distinct manner in accordance with the business processes that are carried out. Because of this, the data that is stored will not be uniform. As a result, the planning of information systems that integrate college business functions requires the use of enterprise architecture. The Enterprise Architecture Planning (EAP) method, which has been customized to fit within the Zachman framework, is the approach that is taken. This study will ultimately result in the production of a blueprint that will serve as the basis for the planning of an information system. The research was carried out over the course of seven stages. The initial phase of the research into the EAP and the Zachman framework, which focuses on the literature. The second stage is the gathering of data, which consists of making firsthand observations at universities and conducting interviews with the director of the SIMFOKOM UIR division. In the third stage, you will initiate the planning that will decide the scope of the EAP, as well as the initialization of the college's vision and mission statements. In the fourth stage, a business modeling analysis will be carried out. The fifth step provides an overview of the present circumstances at the college. This is the sixth step of the planning process for the data architecture, application architecture, and technology architecture. The final step is developing a strategy for carrying out the decisions made during the architectural planning stage. The findings of this research were presented in the form of blueprints, which may be utilized by businesses for the purpose of system planning in educational institutions.